Solid-state separation of hypoxanthine tautomers through a doping strategy. Issue 18 (14th April 2022) - Xue, Rongrong; Liang, Chengfeng; Li, Yanping; Chen, Xiuzhi; Li, Fuying; Ren, Shizhao; Chen, Fenghua
Abstract : The solid-state separation of hypoxanthine tautomers was realized by a doping strategy. The doping forms of hypoxanthine in HAmG, AG β and AG α are N7 -hypoxanthine, and in GM and dehydrated-GM are N9 -hypoxanthine. Abstract : Hypoxanthine is the doping component in anhydrous guanine β (AG β) biominerals. In this work, hypoxanthine was doped into all the reported guanine phases by solution methods. N7 -Hypoxanthine was doped into hydrated amorphous guanine (HAmG), anhydrous guanine β form (AG β) and anhydrous guanine α form (AG α) consisting of N7 -guanine, and N9 -hypoxanthine was doped into guanine monohydrate (GM) and dehydrated-GM consisting of N9 -guanine confirmed by FT-IR, Raman, and ss-NMR. We realized the separation of hypoxanthine tautomers in the solid state by using the principle of doping. This strategy would shed light on the solid-state separation of organic molecular tautomers.